PENGARUH MOTIVASI INTRINSIK, PENGEMBANGAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MARKETING PADA PT AGUNG AUTOMALL CABANG SOEKARNO HATTA PEKANBARU - Zul Fadhli Annur; Samsir '; Marzolina ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted at PT. Agung Automall branch of Soekarno-Hatta in the Soekarno-Hatta Arengka road No.13, Pekanbaru. Objective to analyze the influence of intinsik motivation, development and compensation on performance marketing employees at PT Agung Automall Branch Soekarno Hatta simultaneous and partial. And to know the variables that influence the most powerful employee on performance marketing PT Agung Automall Soekarno-Hatta Pekanbaru Branch of variable intrinsic motivation, development and compensation. To achieve that goal done research using a sample of the population and 52 people. Method of data collection is the questionnaire. The Data were processed using the technique of multiple linear regression analysis of data and with the help of computer software, SPSS. Based on the results of the analysis note that the variables intrinsic motivation, development and compensation effect significantly to performance marketing. The variable that has the most powerful influence on performance is variable development. As the author can submit recommendations to further enhance the more intrinsic motivation, compensation and employee development marketing. Because in these variables greatly influence the performance of marketing employees in the exercise of activities in companies. To further improve the employee's performance marketing again to maximum, the company should pay more attention to intrinsic motivation and compensation of employees by way of creating a conducive working environment as well as increased incentives.Keywords: Intrinsic Motivation, Development, Compensation and Employee Performance